2015
DOI: 10.1128/genomea.00966-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Pseudomonas sp. Strain LFM046, a Producer of Medium-Chain-Length Polyhydroxyalkanoate

Abstract: Pseudomonas sp. LFM046 is a medium-chain-length polyhydroxyalkanoate (PHAMCL) producer capable of using various carbon sources (carbohydrates, organic acids, and vegetable oils) and was first isolated from sugarcane cultivation soil in Brazil. The genome sequence was found to be 5.97 Mb long with a G+C content of 66%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…This species accumulates at least 60% (w/w) of its biomass as PHA MCL , when grown under nitrogen and phosphate limitation [Gomez, 2000;Sánchez et al, 2003;Diniz et al, 2004;Taciro, 2008;Silva-Queiroz et al, 2009]. Metabolic pathways involved in PHA production by this bacterium have been analyzed based on 13 C-labelling experiments [Riascos et al, 2013], and its genome was recently sequenced and annotated by our research group, confirming that the PHA operon phaC1ZC2 is encoded [Cardinali-Rezende et al, 2015]. Differently from other studies producing P[3HB-co-3HA MCL ], previous studies by our research group have indicated the production of PHA copolymers containing 3HA SCL and 3HA MCL from glucose as the sole carbon source when Ralstonia eutropha or Aeromonas spp.…”
Section: Introductionmentioning
confidence: 83%
“…This species accumulates at least 60% (w/w) of its biomass as PHA MCL , when grown under nitrogen and phosphate limitation [Gomez, 2000;Sánchez et al, 2003;Diniz et al, 2004;Taciro, 2008;Silva-Queiroz et al, 2009]. Metabolic pathways involved in PHA production by this bacterium have been analyzed based on 13 C-labelling experiments [Riascos et al, 2013], and its genome was recently sequenced and annotated by our research group, confirming that the PHA operon phaC1ZC2 is encoded [Cardinali-Rezende et al, 2015]. Differently from other studies producing P[3HB-co-3HA MCL ], previous studies by our research group have indicated the production of PHA copolymers containing 3HA SCL and 3HA MCL from glucose as the sole carbon source when Ralstonia eutropha or Aeromonas spp.…”
Section: Introductionmentioning
confidence: 83%
“…Considering those Y Xr/P values for E. coli and Pseudomonas, B. sacchari biomass composition presents lower phosphorus amounts. Also, as phosphorus is a significant component of nucleic acids, it should be noted that B. sacchari genome size is 7.2 Mb (Alexandrino et al, 2015), E. coli K-12 MG1655 genome size is 4.6 Mb (Blattner et al, 1997), and Pseudomonas LFM046 genome size is 6.0 Mb (Cardinali-Rezende et al, 2015). In addition, phospholipids are also important components synthesized from phosphorus.…”
Section: Growth Phasementioning
confidence: 99%
“…Estas modificações se basearam em dados obtidos do draft do genoma de Pseudomonas sp. LFM046 recentemente publicado, além de outros estudos da literatura(Cardinali-Rezende et al, 2015;…”
unclassified